Tuberculosis in the European Union and European Economic Area: a survey of national tuberculosis programmes. Issue 6 (6th December 2018) - Collin, Simon M.; de Vries, Gerard; Lönnroth, Knut; Migliori, Giovanni Battista; Abubakar, Ibrahim; Anderson, Sarah R.; Zenner, Dominik
How many European Union (EU) and European Economic Area (EEA) countries have national tuberculosis (TB) control plans/strategies, and what are the priority actions/populations and barriers to implementation? In order to answer this question, a survey of EU/EEA national TB programme leads was undertaken. The response rate was 100% (31 countries). 55% of countries reported having a national TB strategy, all of which were in implementation; five countries were preparing a strategy. 74% had a defined organisational TB control structure with central coordination and 19% had a costed programme budget; few organisational structures included patient/civil society representation. The most frequently mentioned priority TB control actions were: reaching vulnerable population groups (80%), screening for active TB in high-risk groups (63%), implementing electronic registries (60%), contact tracing and outbreak investigation (60%), and tackling multidrug-resistant TB (60%). Undocumented migrants were the most commonly (46%) identified priority population. Perceived obstacles to implementation included barriers related to care recipients (lack of TB knowledge, treatment seeking/adherence), care providers (including need for specialist training of nurses and doctors) and health system constraints (funding, communication between healthcare and social care systems). This survey has provided an insight into TB control programmes across the EU/EEA that will inform the development of a TB strategy toolkit for member states. There is a need for national TB control plans and investment in human resources to work towards TB elimination across the EU/EEA http://ow.ly/8gZG30m961Y